Importin 13-dependent axon diameter growth regulates conduction speeds along myelinated CNS axons - Jenea M. Bin; Daumante Suminaite; Silvia K. Benito-Kwiecinski; Linde Kegel; Maria Rubio-Brotons; Jason J. Early; Daniel Soong; Matthew R. Livesey; Richard J. Poole; David A. Lyons (Nature Communications, 2024)
Abstract Axon diameter influences the conduction properties of myelinated axons, both directly, and indirectly through effects on myelin. However, we have limited understanding of mechanisms controlling axon diameter growth in the central nervous system, preventing systematic dissection of how manipulating diameter affects myelination and conduction along individual axons. Here we establish zebrafish to study axon diameter. We find that importin 13b is required for axon diameter growth, but does not affect cell body size or axon length. Using neuron-specific ipo13b mutants, we assess how reduced axon diameter affects myelination and conduction, and find no changes to myelin thickness, precision of action potential propagation, or ability to sustain high frequency firing. However, increases in conduction speed that occur along single myelinated axons with development are tightly linked to their growth in diameter. This suggests that axon diameter growth is a major driver of increases in conduction speeds along myelinated axons over time.